Child maltreatment, subsequent non-suicidal self-injury and the mediating roles of dissociation, alexithymia and self-blame - Swannell, S.; Martin, G.; Page, A.; Hasking, Penelope; Hazell, P.; Taylor, A.; Protani, M. (Elsevier Limited, 2012)
Objective: Although child maltreatment is associated with later non-suicidal self-injury (NSSI), the mechanism through which it might lead to NSSI is not well understood. The current retrospective case-control study examined associations between child maltreatment and later NSSI, and investigated the mediating roles of dissociation, alexithymia, and self-blame. Methods: Participants were 11,423 Australian adults (response rate 38.5%), randomly selected from the Australian Electronic White Pages, aged between 18 and 100 (. M=. 52.11, . SD=. 16.89), 62.2% female. Data were collected via telephone interviewing. Main outcome measures were reported history of child maltreatment (sexual abuse, physical abuse, neglect) and reported 12-month NSSI. Dissociation, alexithymia, and self-blame were examined as potential mediating variables in the relationship between child maltreatment and later NSSI. All analyses were conducted using logistic regression and adjusted for age and psychiatric diagnosis. Results: Results differed by gender. Compared to no child maltreatment, physical abuse (OR 2.75, 95% CI 1.68-4.51) and neglect (OR 2.56, 95% CI 1.65-3.99) independently increased the odds of NSSI among females. Physical abuse (OR 2.69, 95% CI 1.44-5.03) increased the odds of NSSI among males. Sexual abuse did not independently increase the odds of NSSI for males or females. For females, self-blame had the greatest effect on the child maltreatment-NSSI relationship (OR decreased by 14.6%, . p<. .000), although dissociation and alexithymia also partially mediated the relationship. For males, dissociation had the greatest effect (OR decreased by 12.9%, . p=. .003) with self-blame also having a relatively strong effect. Conclusions: The results indicate that child maltreatment, and in particular, physical abuse, is strongly associated with the development of subsequent NSSI and may be partially mediated by dissociation, alexithymia, and self-blame for females and dissociation and self-blame for males. Altering attributional style (through cognitive therapy or emotion focussed therapy) and improving the capacity to regulate emotions (through dialectical behaviour therapy) may contribute to reduction or cessation of NSSI.